2003
DOI: 10.1007/s00104-003-0721-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotische Behandlung der sekund�ren Peritonitis in Deutschland

Abstract: Based on clinical, bacteriological, and pharmacoeconomic results, ceftriaxone in combination with metronidazole can be regarded as a first-line antimicrobial treatment of secondary peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
1
0
1
Order By: Relevance
“…The choice of antibiotics seem to rely to a large extend on the fact that E. coli has been identified as the most frequent causative agent [ 8 , 40 ]. Its sensitivity pattern validates our choice of antibiotics combination which elements are very widely used [ 40 , 41 ], although some studies have reported other germs with a different sensitivity pattern [ 42 ]. The replacement of 3 rd generation cephalosporin by ampicillin in the protocol has been proved to be a valid cost-effective regimen, especially if combined with gentamicin [ 43 ].…”
Section: Discussionmentioning
confidence: 79%
“…The choice of antibiotics seem to rely to a large extend on the fact that E. coli has been identified as the most frequent causative agent [ 8 , 40 ]. Its sensitivity pattern validates our choice of antibiotics combination which elements are very widely used [ 40 , 41 ], although some studies have reported other germs with a different sensitivity pattern [ 42 ]. The replacement of 3 rd generation cephalosporin by ampicillin in the protocol has been proved to be a valid cost-effective regimen, especially if combined with gentamicin [ 43 ].…”
Section: Discussionmentioning
confidence: 79%
“…B. Acylaminopenicillin/Betalactamase-Inhibitor, Breitbandcephalosporin/Metronidazol oder Ertapenem. Die Kombination Ceftriaxon/Metronidazol stellt hier eine auch ö komomisch sinnvolle Wahl dar [26]. Die Gabe sollte idealerweise prä operativ, spä testens aber intraoperativ erfolgen [25,27].…”
Section: Antibiotikatherapieunclassified